The homeless population during the COVID-19 syndemic: Inequities, practices of social resilience, and social reintegration strategies - Bova, Roberta (Frontiers in Sociology, 2022)
This paper analyses the amplification of social insecurity and the social misrecognition of the homeless during the COVID-19 pandemic. The research was carried out in the city of Bergamo (IT), which has been severely affected by the COVID-19 pandemic since the early months of 2020; the research was developed in two phases. The first one analyses the practices of social resilience activated during the COVID-19 pandemic by the socio-educational staff and the coordination figures who work in the support services. The second phase analyses the different social dynamics that can improve the well-being and social reintegration of the homeless, in a long-during prospective. During the first months of 2020, the public authorities failed to pay attention to homeless people, both those who slept on the streets and those who lived in communities or found support in night shelters. The support services had to activate immediate emergency response strategies and subsequently had to produce and purchase the protective devices for operators, guests and those who remained on the street. Faced with this process of social misrecognition, the support services for homeless people reacted by activating practices of social resilience. These practices have been investigated both in the dimension of daily interactions and in the symbolic and value configurations connected to them. However, from directly conversing with the homeless it emerges that, in order to achieve full social reintegration and to prevent new forms of social misrecognition, in the event of future social or health crises, the relationship with a non-stigmatised social community is fundamental. Consequently, the primary objectives that the support network for homeless people should set for future projects should be to involve the local community through project participation activities and raising awareness of the phenomenon of poverty.